THYROID SURGERY: A COMPARISON OF COMMON COMPLICATIONS BETWEEN EXPERTS AND SURGEONS IN TRAINING - Shabbir Bukhar, Syed Muhammad Asad; Hassan, Zaheer Ul; Butt, Kamran Ashfaq; Riaz, Naeem; Akram, Chaudhry Muhammad Bilal; Shah, Amanat Ali (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of common complications of thyroid surgery by two types of surgeons.Study Design: Comparative cross sectional.Place and Duration of Study: Combined Military Hospital Rawalpindi & Combined Military Hospital Peshawar, from Jan 2013 to Dec 2017.Methodology: This study was conducted to assess the role of surgical skills in complications of thyroid surgery. Surgeons performing surgery for more than 5 years were considered expert and less than 5 years of experience were considered trainee for this specific surgery. Complications by both were analyzed by SPSS-21 and descriptive statistics were applied.Results: A total of 482 surgeries were performed. Out of 407 were female and 75 were males. Mean age was 43.55 ± 10.9 years. Expert surgeons performed 300 cases and 16 (5.3%) experienced some complication in 6 months of follow up.182 cases were performed by surgeons with lesser experience and 14 (7.5%) cases developed complications over the period of follow up. Recurrent laryngeal nerve paralysis occurred in 2 (0.67%) of experienced surgeons cases while 6 cases (3.2%) of less experienced surgeons had the similar complication.Conclusion: While the overall complication rates are not much different between experienced and lesser experienced surgeons, the rate of recurrent laryngeal nerve paralysis is significantly more, though still within the acceptable international complication rate for this particular surgery.